Neo-scholastic ideas on Belarusian historical and cultural space - Liahchylin, Anatoli A.; Klimovich, Hanna I. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article researches the main milestones in the development neo-scholastic tradition within the Belarusian religious and philosophical thought, the basic facts of life and creative ways of its representatives. Neo-scholastic tradition in Belarus has deep roots and a rich history. It is possible to identify two periods in its framework: Polack period and Druja period. The ideas, which had the basic positions for the philosophical direction of the first period, are present also in the second, it shows the continuity of principles. The facts suggest, that the Polack Jesuit Academy was the place where neo-sholastic ideas were stored before their returning to the European philosophical space. They became an impetus for the development of neo-Thomism movement, and then returned to Belarus in the works of Belarusian thinkers.